The pathophysiology and therapy of erectile dysfunction in a newly discovered treatise by Wolfgang Reichart (1486-circa 1547) - Ursin, Frank; Rubeis, Giovanni; Steger, Florian (Urology, 2020)
Background - A newly-found treatise by Wolfgang Reichart (1486-circa 1547), town physician of Ulm, challenges the contemporary view that bewitchment as a cause of impotence defies any natural explanation. - Objective - To understand the pathophysiological concept and therapy of erectile dysfunction in Reichart's treatise by examination of his sources and previous concepts. - Methods - Source analysis of Reichart's treatise by comparison of the pathophysiological concepts and therapy of erectile dysfunction with original texts of the Corpus Hippocraticum (5th-3rd century BC) and Constantinus Africanus (11th century). - Results - By using rational thinking and medical knowledge mainly drawn from antiquity, especially Constantinus Africanus, Reichart shows that a supposed supernatural cause for impotence can be explained by reason and natural means. Reichart's treatise changes the view of bewitchment as cause of impotence. He makes eclectical use of previous concepts to explain his patient's condition. From the Middle Ages on, bewitchment was accepted as a cause for erectile dysfunction. Usually, physicians of that time accepted this etiology and advised a treatment based on theological concepts. Reichart challenges this view by emphasizing reason and medical knowledge as crucial for treating the patient, rejecting supernatural treatment approaches. - Conclusions - In the 16th century, a type of rational thinking and medical knowledge emerges, which puts supernatural explanations into question and aims at treating patients with natural means. The analysis of Reichart's treatise is a much-needed contribution to understanding the historic development of pathophysiological concepts of and therapeutic measures for impotence, which is yet underresearched.
Gesehen am 22.07.2020